2017
DOI: 10.5114/fmpcr.2017.67863
|View full text |Cite
|
Sign up to set email alerts
|

Does anybody support the supporters? Social support in the cancer patient-caregiver dyad

Abstract: A -study Design, B -Data Collection, C -statistical analysis, D -Data Interpretation, E -Manuscript Preparation, F -Literature search, G -Funds CollectionBackground. Cancer and its treatment enforce changes in patient functioning. the principal objective of each patient is to efficiently cope with the disease, i.e. to completely recover or at least to slow its progression. Under such circumstances, patients and their relatives require various forms of support: emotional, informational and instrumental. Objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…The level of this support determines the SOC of caregivers which, as demonstrated above, is a key resource in coping with the disease within patient–caregiver dyad. The previous Polish study analysing the role of social support in cancer patients and their caregivers not only demonstrated that the former receive less support from a smaller number of sources; we also showed that compared to patients, caregivers receive less support of any type from medical personnel (Dębska et al., ). This implies that management of cancer patients should include also interventions addressed to their caregivers, and particular emphasis should be put on strengthening caregivers’ support networks, as well as on motivating patients to allow their caregivers to use these networks.…”
Section: Relevance To Clinical Practicesupporting
confidence: 57%
See 2 more Smart Citations
“…The level of this support determines the SOC of caregivers which, as demonstrated above, is a key resource in coping with the disease within patient–caregiver dyad. The previous Polish study analysing the role of social support in cancer patients and their caregivers not only demonstrated that the former receive less support from a smaller number of sources; we also showed that compared to patients, caregivers receive less support of any type from medical personnel (Dębska et al., ). This implies that management of cancer patients should include also interventions addressed to their caregivers, and particular emphasis should be put on strengthening caregivers’ support networks, as well as on motivating patients to allow their caregivers to use these networks.…”
Section: Relevance To Clinical Practicesupporting
confidence: 57%
“…Consequently, caregivers should receive social support. Unfortunately, a large body of evidence implies that in fact they suffer from support deficits (Chen et al., ; Dębska, Pasek, & Wojtyna, ; Sklenarova et al., ). Also in our study, the level of perceived support in caregivers turned out to be lower than in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study site was determined by the inclusion criteria of the research and can be categorised into two main types. The first type ( n = 7) included oncology departments that provided radiotherapy and clinical oncology/chemotherapy [ 10 , 23 , 26 , 31 ], hospitals, or oncology hospitals [ 25 , 27 , 28 ], where cancer patients treated with anticancer drugs were recruited. The second type consisted of wards ( n = 6), where patients with specific clinical diagnoses were hospitalised, such as gastric cancer [ 29 ], head and neck cancer [ 32 ], colorectal cancer [ 30 ], breast cancer [ 24 ] and genital cancer [ 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…A multinational study which examined the association between social support and mental wellbeing among adolescents reported that increased perception of social support from a caring family member or significant others negatively correlated with the severity of depressive symptoms (Cheng et al, 2014). Apart from the adolescent population, the importance and influence of social support have been described among diverse populations such as caregivers of patients with oncological disorders (Dębska, Pasek, & Wojtyna, 2017), individuals with sudden loss of auditory function (Hricová, 2018), patients receiving treatment for rheumatoid arthritis (Akintayo et al, 2018) and nursing students (Zarzycka, Ślusarska, Dyk, Bednarek, & Trojanowska, 2018).…”
Section: Introductionmentioning
confidence: 99%